Bilateral Trade in European Sports Industry: Linder Versus Hecksher-Ohlin-Samuelson - Kazar, Gorkemli; Kazar, Altug; Sert, Tamer Sami (International Journal of Economics and Financial Issues, 2018)
In recent years, sports industry became one of the diverse industries in the World. Its inter-industry and intra-industry trade potential revitalize the national economies, especially in Europe. Therefore, this paper examines the determinants of bilateral industrial sports sector trade in twenty-eight European countries. Following the relative endowment-based gravity model, the econometric estimates of the panel datasets show that bilateral trade increases with the size of domestic markets and the similarity of the country size. However, the trade volume is negatively affected by the transportation costs. According to simulation results, the appreciation of the domestic currency has a negative effect on trade volume except the inland Visegrad countries. The Linder hypothesis is validated only for countries with large market shares. So, most of the European countries improve their bilateral trade through factor endowment differences. Keywords: Europe, Endowment-Based Gravity Model, Sports Industry Trade JEL Classifications: F1, L83, O52